2016
DOI: 10.22282/v5.i4.01
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Sports High School Students Coping With Stress Levels

Abstract: This study, aims to examine the different variables in how the students in sports high school copes with stress. In this study, screening method has been used and 242 questionnaires were distributed to the participants by the number of students. Out of 204, 201 has been returned. Some of these questionnaires has been without valid reasons, such as incomplete questionnaires are set to leave. In total, 188 of the questionnaires has been found worthy of analysis. Accordingly, 188 participant's information (% 68.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
1
0
1
Order By: Relevance
“…This finding perhaps could be linked to the similarity in the geographical contexts in which the studies were conducted (i.e., West Africa). However, the current finding disagrees with other past studies [40][41][42][43]. For example, Kim [44] identified gender variations in the pattern of associations between religiosity and externalizing problems, that is, religious attendance was associated with externalizing problems among non-maltreated boys, but not among ill-treated boys or girls.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding perhaps could be linked to the similarity in the geographical contexts in which the studies were conducted (i.e., West Africa). However, the current finding disagrees with other past studies [40][41][42][43]. For example, Kim [44] identified gender variations in the pattern of associations between religiosity and externalizing problems, that is, religious attendance was associated with externalizing problems among non-maltreated boys, but not among ill-treated boys or girls.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, age of student-athletes had no influence on their positive and negative religious coping strategies, a finding that corroborates a previous study [43]. Notwithstanding, another previous study reported a contrary finding [41].…”
Section: Discussionsupporting
confidence: 88%